2018
DOI: 10.1111/1742-6723.13095
|View full text |Cite
|
Sign up to set email alerts
|

Arterial to end‐tidal carbon dioxide tension difference (CO2 gap) as a prognostic marker for adverse outcomes in emergency department patients presenting with suspected sepsis

Abstract: In this pilot study of patients with suspected sepsis from non-respiratory causes, an increased CO gap demonstrates value in risk stratification and needs to be further evaluated and compared to other existent biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Post-hoc power analysis showed we had 63% power (alpha error of 5%) to detect ROSC in OHCA patients with this sample size. In the literature, it has been reported that ΔCO 2 cut-off values vary between 9 and 10.6 mmHg, according to different outcome measures (6,7,9,16). In our study, the optimal cutoff value for ΔCO 2 in predicting ROSC in OHCA patients was 51.4 mmHg.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Post-hoc power analysis showed we had 63% power (alpha error of 5%) to detect ROSC in OHCA patients with this sample size. In the literature, it has been reported that ΔCO 2 cut-off values vary between 9 and 10.6 mmHg, according to different outcome measures (6,7,9,16). In our study, the optimal cutoff value for ΔCO 2 in predicting ROSC in OHCA patients was 51.4 mmHg.…”
Section: Discussionmentioning
confidence: 52%
“…Ischemia-reperfusion injury after cardiac arrest causes pulmonary and cardiovascular damage and increases the gap between pCO 2 and ETCO 2 . This gap, which should normally not exceed 3-5 mmHg, is called ΔCO 2 (5)(6)(7). A high ΔCO 2 was reported to have a significant relationship with mortality or poor outcomes in aspiration pneumonia, pulmonary edema, acute respiratory distress syndrome, trauma surgery, and pulmonary embolism (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shetty et al evaluated 215 patients presenting to the emergency department (ED) and the arterial-ET difference modestly predicted adverse outcomes in patients presenting with suspected sepsis due to non-respiratory causes. Those with normal arterial-ET differences were noted to have much lower risk for hospital mortality and prolonged ICU length of stay [ 23 ]. Yamanaka et al [ 24 ] studied 17 patients requiring endotracheal intubation and mechanical ventilation using an average of exhaled PCO 2 at the end of several breaths over a duration of 30 s and found that the difference between arterial and exhaled CO 2 correlated closely with physiological dead space ( r = 0.80, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…However, 95% ULA values of the P ET CO 2 –PaCO 2 gradient were determined in the range of 13.01–15.04 mmHg, and these results are quite high compared to the literature [ 19 ]. In diseases that cause hemodynamic instability, such as sepsis and shock, P ET CO 2 measurements tend to be higher than corresponding PaCO 2 measurements [ 41 ]. High 95% ULA values in our study may be associated with the presence of patients with hemodynamic instability (such as shock and multi-trauma diagnoses) in our study, and the analysis of the highest number of measurement values in the literature so far (1118 pairs).…”
Section: Discussionmentioning
confidence: 99%